A Glance at International Curriculum Perspectives. Towards a Democratic, Deliberative and Living Curriculum - Hugo Rangel Torrijo (Universidad Autónoma de Baja California, 2014)
This paper presents a reflection on the main principles (theoretical and socio-political) involved in the formulation of a curriculum proposal. We note the tension between the respective positions of a formal or set curriculum versus a hidden or lived curriculum. We argue that it is imperative that this unnecessary polarization be left behind by means of a democratic proposal of curricular policy. We posit an approach that we call living curriculum, a proposal that is, on the one hand, anchored in social practices and, on the other, entails the amalgamation of the component stages of the curriculum. It involves a democratic process of curriculum renewal, since its implementation must be participatory in order for it to be anchored in social practices. Likewise, it must involve an evaluation that mobilizes stakeholders and generates knowledge for the renewal of both the curriculum as well as the educational institutions.